Information Management: Learning Things Outside Textbooks - Silveira, Teresa Joana da Silva (The Canadian Journal of Information and Library Science / La Revue canadienne des sciences de l’information et de bibliothéconomie, 2024)
The world changed. More than ever information gains a strategic role in professional contexts. Organizations are told that they will not survive in the modern era without a strategy for managing and leveraging value from information (extended to knowledge). This means that organizations must change the way information is managed, from a “housekeeping” style to a transversal mode, similar to how Human Resources, Finance, or Information Technology departments. This paper recommends some actions to make information/knowledge management an asset to be measured and with an impact on career development. It is a qualitative analysis resulting from an exploratory literature review and its comparison with working experience and observation in the last 15 years as an information manager. Via this combination, it was possible to approach a different type of intellectual capital investment, resulting in the proposal of creating an information/knowledge ladder strategy followed by a new performance evaluation indicator resulting from the information/knowledge management investments. The key conclusion shows that although information/knowledge management is a key asset for success, it’s necessary to reinforce research and implementation studies in strategies that measure the returns on information/knowledge investments. It’s also fundamental to the role of the academic side, extra engaging with organizations but also investing more in studies and creating new measurement techniques and indicators to be explored by future information professionals, particularly information managers.